A review of the spatial distribution of and analytical techniques used in paleotempestological studies in the western North Atlantic Basin. (April 2017) - Oliva, Frank; Peros, Matthew; Viau, André
Paleotempestology, the study of past tropical cyclones (TCs) using geological proxy techniques, is a growing discipline that utilizes data from a broad range of sources. Most paleotempestological studies have been conducted using "established proxies, " such as grain-size analysis, loss-on-ignition, and micropaleontological indicators. More recently, however, researchers have been applying more advanced geochemical analyses, such as X-ray fluorescence core scanning and stable isotopic geochemistry, to generate new paleotempestological records. In this paper we begin by providing a list of paleotempestological studies for the western North Atlantic Basin and illustrate the spatial coverage of these studies. We then review the premises behind both established and new proxies and discuss their strengths and limitations at resolving past hurricane activity. Lastly, we suggest future directions for paleotempestological research based on our review of the literature that we argue will ultimately lead to a better understanding of TC dynamics under future climate change scenarios.